2007
DOI: 10.1097/01.ncc.0000265004.64440.5f
|View full text |Cite
|
Sign up to set email alerts
|

Resting Energy Expenditure and Body Mass Changes in Women During Adjuvant Chemotherapy for Breast Cancer

Abstract: Weight gain is a commonly reported side effect of adjuvant chemotherapy. A change in resting energy expenditure during treatment has been a suggested mechanism for weight gain. We prospectively measured resting energy expenditure, weight change, and body composition (dual-energy x-ray absorptiometry) in 10 women undergoing adjuvant chemotherapy for breast cancer. There was no change in resting energy expenditure across cycles of chemotherapy (P =.78) or from baseline to the end of treatment (1,189.68 +/- 80.27… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
56
1
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 33 publications
10
56
1
4
Order By: Relevance
“…Changes in BMI during anthracycline-based CTx have been associated with poorer prognosis, in terms of increased recurrence and mortality rates 13,14 . However, other studies have recorded only slight weight gains or unchanged weight with anthracycline-based regimens 22,24,32 .…”
Section: Discussionmentioning
confidence: 99%
“…Changes in BMI during anthracycline-based CTx have been associated with poorer prognosis, in terms of increased recurrence and mortality rates 13,14 . However, other studies have recorded only slight weight gains or unchanged weight with anthracycline-based regimens 22,24,32 .…”
Section: Discussionmentioning
confidence: 99%
“…A small study by Campbell et al [34] followed 10 women undergoing adjuvant chemotherapy and measured resting energy expenditure using dual energy x-ray absorptiometry across cycles of treatment. Although participants did not gain weight, and there was no change in resting energy expenditure, there was an increase in total fat mass.…”
Section: Menopause and Age Effectmentioning
confidence: 99%
“…While some retrospective studies identified a number of potential patient and therapy-related factors associated with weight gain over time, the reasons for postdiagnosis weight gain have not been clearly identified. Chemotherapy (CT), being or becoming postmenopausal after diagnosis, decreased physical activity, dietary factors such as increased caloric intake, psychosocial factors have all been implicated for postdiagnosis weight gain in patients with early BC [8,9,17,[19][20][21][22][23]. It is important to know that all studies showing evidence of significant weight gain following adjuvant treatment were reported from the United States and Western European countries.…”
Section: Introductionmentioning
confidence: 99%